Ad-Dalālah aṣ-Ṣautiyah li Ḥurūf ar-Rawiy fī Dīwān “Syajar El-Lail” li Salah Abdel Sabbour: الدلالة الصوتية لحروف الروي في ديوان "شجر الليل" لصلاح عبد الصبور - Muhammad Zakaria Darlin; Sherif Alalfy (LISANIA: Journal of Arabic Education and Literature, 2024)
The narration letters were multiplied in the free verse (free poetry) of its first pioneer in Egypt, the poet Salah Abdel Sabbour, violating the rules of rhyme established by al-Khalil. In the opinion of his followers, this may spoil the unity of the poem's meaning and lead to the corruption of the entire poem. The researchers tried to respond to these old critical opinions by discovering the hidden secrets behind these various rhymes by using stylistic and structural methodologies in addition to literature statistics, to justify the sincerity of the emotion of this new poetry and the extent of its interaction with the conditions of time and place in which the poetry is said. The researchers will apply it in his poetry collection "The Trees of the Night". The stylistic characteristics of these contemporary poems are going to be the proven evidence on the phonetic level in front of the reader. We found that the diversity of the last letter within the poem has enriched the meaning, making the poetry richer in meaning, and at the same time did not diminish the poetic energies.